2019
DOI: 10.1210/jc.2019-00461
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Adipose Tissue Reveals Depot-Specific Metabolic Alterations Among Patients with Colorectal Cancer

Abstract: Context Adipose tissue inflammation and dysregulated energy homeostasis are key mechanisms linking obesity and cancer. Distinct adipose tissue depots strongly differ in their metabolic profiles; however, comprehensive studies of depot-specific perturbations among patients with cancer are lacking. Objective We compared transcriptome profiles of visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) from patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 89 publications
0
27
0
Order By: Relevance
“…We found that in ammatory genes such as IL-6 and TNF-α were actually expressed at lower levels in obese ACs than in lean ACs, indicating that in ammatory genes are downregulated in the obese condition. In fact, contrary to what was conventionally believed, several recent studies have reported that obese ATs do not show increased expression of in ammatory genes, as described in the Background section [27,28]. In addition, studies addressing the possible enhancement of in ammatory genes by analyzing DEGs between obese ATs and lean ATs collected from obese and lean cohorts, respectively, are surprisingly rare.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We found that in ammatory genes such as IL-6 and TNF-α were actually expressed at lower levels in obese ACs than in lean ACs, indicating that in ammatory genes are downregulated in the obese condition. In fact, contrary to what was conventionally believed, several recent studies have reported that obese ATs do not show increased expression of in ammatory genes, as described in the Background section [27,28]. In addition, studies addressing the possible enhancement of in ammatory genes by analyzing DEGs between obese ATs and lean ATs collected from obese and lean cohorts, respectively, are surprisingly rare.…”
Section: Discussionmentioning
confidence: 84%
“…However, we think this is unlikely because the in uence of cancer over changes in gene expression in AT between the lean and obese conditions are mutually offset in the gene expression pro les and would not be detected in the DEG analysis. Moreover, Haffa et al (2019) showed that the correlation between obesity and AT gene expression exceeds the potential impact of colorectal cancer or cancer therapy when investigating the expression of genes in SAT and VAT from 233 colorectal cancers [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that in ammatory genes such as IL-6 and TNF-a were actually expressed at lower levels in obese ACs than in lean ACs, indicating that in ammatory genes are downregulated in the obese condition. In fact, contrary to what was conventionally believed, several recent studies have reported that obese ATs do not show increased expression of in ammatory genes, as described in the Background section [28,29]. In addition, studies addressing the possible enhancement of in ammatory genes by analyzing DEGs between obese ATs and lean ATs collected from obese and lean cohorts, respectively, are surprisingly rare.…”
Section: Discussionmentioning
confidence: 84%
“…According to Rakotoarivelo et al (2018), the expression of in ammatory cytokines such as IL-6, TNF-a and IL-1b in AT is highly heterogeneous among obesity-associated diabetes patients, and 30% of obese patients do not express most of these in ammatory cytokines in the AT [28]. Haffa et al (2019) showed that these cytokines do not show obesity-related gene expression levels in AT [29]. Baranova et al (2005) reported a paradoxical decrease in the expression of pro-angiogenic genes, which is another gene class that is expected to increase in obese individuals [30].…”
Section: Introductionmentioning
confidence: 99%